Therapeutic angiography and embolisation for bleeding aberrant duodenal artery arising from replaced hepatic artery. (15th November 2013) - Azeemuddin, Muhammad; Naqi, Rohana; Sayani, Raza
Abstract : We present a rare case of a 70-year-old man with a known case of hypertension and carcinoma larynx, he was admitted under ENT (ear, nose and throat) services for a laryngectomy. On admission, he started having severe per rectal bleeding. The patient underwent a number of radiological investigations to determine the origin of the bleed, including Tc 99 m labelled red blood cells tagged scan, a CT scan and two angiographies. The final angiogram showed an aberrant artery supplying the duodenum showing active extravasation. It was arising from the replaced right hepatic artery which itself arose from the superior mesenteric artery. Successful embolisation was performed using polyvinyl alcohol particles and microcoil. We present this rare case of an aberrant artery supplying the duodenum.